Reservoir characteristic and its relationship with estimated ultimate recovery of Jurrasic tight shelly limestone reservoir in the central Sichuan Basin, Southwest China. (6th July 2022) - Wang, Shaoyong; Wang, Yuan; Li, Denghua
A combination of reservoir geological factors and a decline curve approach were applied in a play wide analysis, to reveal the relationship between the reservoir characteristics and estimated ultimate recovery (EUR) of the tight shelly limestone reservoir of Da'anzhai formation. As a result, all the oil bearing matrix pores and fractures in the reservoir correspond to the exponential decline, logarithmic decline and power law exponential decline with diminishing EURs of 86.1 MSTB, 39.3 MSTB and 5.9 MSTB (Mille Standard Tank Barrel) (P50) respectively. The proportions of megapores, macropores, mesopores, micropores, and nanopores in the reservoir were 1.6%, 3.7%, 18.1%, 27.8% 27.8%, and 48.8% respectively, and the corresponding EUR ranges tended to be above 294 MSTB, 110 MSTB to 294 MSTB, 37 MSTB to 110 MSTB, 4 MSTB to 37 MSTB, and below 4 MSTB. Thicknesses of fracture segments and thickness ratio's of dissolved cave segments to the reservoir were positively linearly related to the EUR. [Received: April 13, 2021; Accepted: November 26, 2021]